THE ROLE OF HIGH TECHNOLOGIES IN TEACHING ENGLISH GRAMMAR - Fayzullayev Jamoliddin Qo`chqor og`li (Bright Mind Publishing, 2025)
Despite significant developments in language teaching methods in past years, language teachers also face the challenge of determining the status of teaching grammar (Ellis, 2003, 2006). Grammar should be taught or create a situation where language learners can naturally learn grammar (Ellis, 2006). In this view, teachers should be well aware of the differences between grammar knowledge and grammar competence. Grammar may be described as the comprehension of sentence structure patterns and grammar as a tool in producing spoken and written texts (Richards & Reppen, 2014). Teachers use recognizable technology for teaching purposes, despite the difficulty of this factor. The technology used for teaching grammar has been the prominent subject of classical and contemporary language teaching studies. Luckily, a wide range of technologies ranging from low-tech, interactive technologies, high-tech options, and increasingly intelligent future options can adapt to meet the learning goals.